Bob Gebhardt interviewed by Alex and Annette Hood in the Alex Hood folklore collection - Gebhardt, Bob, 1922-; Hood, Alex, 1935-; Hood, Annette, 1948- (2002)
Gebhardt recalls his life as a drover, his early days in Broken Hill (N.S.W.). He speaks about his his relationships with his Aboriginal & Afghan mates and co-workers; his work as a master welder of international standing.
Accompanying material: Photographs of the interviewee.
Recorded on May 27, 2002 at Point Clare, N.S.W.
Digital master available
Bob Gebhardt - retired master welder and drover.
Transcript not available.
Keywords: Gebhardt, Bob, -- 1922- -- Interviews; Drovers -- New South Wales -- Interviews; Welders (Persons) -- New South Wales -- Interviews; Drovers; Welders